Surface acoustic wave scattering by elliptic metal disc on anisotropic piezoelectric halfspace - DANICKI, E. (Archives of Acoustics, 1992)
Sufrace acoustic wave (SAW) propagating in arbitrarily anisotropic piezoelectric halfspace is considered. The wave interacts with a perfectly conducting and weightless metal disk on the substrate surface by means of the electric potential only which is coupled to SAW due to the substrate piezoelectricity. A perturbation theory of scattering plane harmonic SAW by the disk is presented which accounts the dielectric, and elastic anisotropy of the substrate. The solution for electric charge distribution on the disk is given in a form of fast convergent series easy for computation. The total electric charge induced by SAW on the grounded disk is explicitly evaluated. Angular dependences of the scattered SAW in large distance from the disk is also discussed.